Preparing and regulating a bi-stable molecular switch by atomic manipulation - S. Sakulsermsuk (2018)
We present a scanning tunneling microscopy (STM) investigation into the influence of the STM tip on the adsorption site switching of polychlorinatedbiphenyl (PCB) molecules on the Si(111)-7×7 surface at room temperature. From an initially stable adsorption configuration, atomic manipulation by charge injection from the STM tip prepared a new bi-stable configuration that switched between two bonding arrangements. No switching rate bias dependence was found for +1.0 to +2.2V. Assuming a thermally driven switching process we find that the measured energy barriers to switching are influenced by the exact location of the STM tip by more than 10%. We propose that this energy difference is due the dispersion interaction between the tip and the molecule. © 2012 IOP Publishing Ltd.